PENEGAKAN HUKUMAN DISIPLIN DAN SANKSI PIDANA TERHADAP APARATUR SIPIL NEGARA YANG MELANGGAR ASAS NETRALITAS DALAM MASA PEMILIHAN UMUM - Rahman, Muhammad Ikhwan; Muchsin, Putri Rofifah Nabila (Muhammadiyah Makassar University, 2024)
ABSTRACT General Elections are a manifestation of people's sovereignty in order to produce a democratic government. which is stated in the 1945 Constitution of the Republic of Indonesia Article 22E. Article 22E of the 1945 Constitution of the Republic of Indonesia states that general elections are held directly, publicly, freely, secretly, honestly and fairly once every five years. General elections are held to elect members of the People's Representative Council, Regional Representative Council, President and vice president and Regional People's Representative Council. In the implementation of elections as regulated in Law 7 of 2017 concerning General Elections, things and limitations are certainly regulated in the implementation of general elections and one of the main concerns in implementing election laws and other regulations is related to the neutrality of the State Civil Apparatus. (called ASN) as state administrators. The approach method used is juridical-normative, with a dogmatic type of research, a descriptive research form of legal relations. The specifications of this research are descriptive-analytical. The data collection method used was the library research method by examining the document and library materials used in this research. In the event that an alleged election violation occurs, it has been regulated in detail and clearly in the Republic of Indonesia General Election Supervisory Agency Regulation Number 7 of 2022 concerning Handling of Findings and Reports of General Election Violations, if the alleged violation by the State Civil Service is related to a violation of the code of ethics then the recommendation can be continued to the State Civil Apparatus Commission (KASN) by the Election Supervisory Agency, while election crimes were handed over to the court after carrying out a series of processes at the Integrated Law Enforcement Center (Gakkumdu) which consists of three agencies, namely Bawaslu, Police and Prosecutor's Office. Keywords: Election, Neutrality of ASN in Elections